2019
DOI: 10.1016/j.vhri.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Collaborative Pharmaceutical Care Service Among Patients With Diabetes in an Ambulatory Care Setting in Qatar: A Multiple Time Series Study

Abstract: Background: Diabetes mellitus is highly prevalent in the Middle East and the burden associated with it is dramatically increasing. Pharmacists working in collaborative healthcare teams have an important role to improve outcomes in the primary care of diabetes. Objectives: To evaluate the impact of a collaborative pharmaceutical care service (CPCS) on improving outcomes among patients with diabetes in a primary care setting. Methods: This was a retrospective, multiple time series study involving patients attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
4
2
0
2
Order By: Relevance
“…In Brazil, a randomized controlled trial conducted in a secondary diabetic care clinic for 80 patients with type 2 diabetes, HbA1C level at baseline was ≥7.0%, and aged 40-79 years demonstrated that the pharmacistphysician collaborative care model had a greater reduction in HbA1c compared to the usual care (-0.79 vs. -0.16; p = 0.010), respectively [12]. Moreover, a retrospective study conducted at an ambulatory diabetes clinic in Qatar showed that the collaborative pharmaceutical care service significantly reduced HbA1c level by 1.4%, fasting plasma glucose (FPG) by 41.3 mg/dL, body mass index (BMI) by 1 kg/m 2 , systolic blood pressure (SBP) by 14.9 mmHg, and diastolic blood pressure (DBP) by 8.7 mmHg from baseline to 12 months (p = 0.001), while there was no significant reduction in the lipid profile [13].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In Brazil, a randomized controlled trial conducted in a secondary diabetic care clinic for 80 patients with type 2 diabetes, HbA1C level at baseline was ≥7.0%, and aged 40-79 years demonstrated that the pharmacistphysician collaborative care model had a greater reduction in HbA1c compared to the usual care (-0.79 vs. -0.16; p = 0.010), respectively [12]. Moreover, a retrospective study conducted at an ambulatory diabetes clinic in Qatar showed that the collaborative pharmaceutical care service significantly reduced HbA1c level by 1.4%, fasting plasma glucose (FPG) by 41.3 mg/dL, body mass index (BMI) by 1 kg/m 2 , systolic blood pressure (SBP) by 14.9 mmHg, and diastolic blood pressure (DBP) by 8.7 mmHg from baseline to 12 months (p = 0.001), while there was no significant reduction in the lipid profile [13].…”
Section: Introductionsupporting
confidence: 89%
“…According to The United Kingdom Prospective Diabetes Study, the clinical consequences for every 1.0% decrease in HbA1c levels are fabulous; because each 1.0% reduction in the HbA1c is accompanied by a relative risk reduction of 21% for any diabetes-related endpoint, 14% for myocardial infarction, 37% for microvascular complications, and 21% for diabetes-related deaths [15]. As mentioned in the literature review, these results are consistent with those of the previous several studies that stated that clinical pharmacist has a crucial role in improving HbA1c among these subjects [11], [12], [13], [14].…”
Section: Discussionsupporting
confidence: 68%
“…Eighty-two per cent of the consumers were using medicines without a prescription, 45% did not complete the antibiotic course and 23% were taking antibiotics from the pharmacy without a prescription in Qatar. 14 Abdulrhim et al 15 concluded that collaborated pharmaceutical care services and pharmacists' interventions would improve clinical outcomes in type 2 diabetes mellitus patients in Qatar. Access to medicines is an essential element of pharmaceutical policy, including equitable access, availability, affordability of medicines, as well as cost-effective use of medicines.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…A pesar de las terapias efectivas disponibles para ayudar a los pacientes a controlar su DM, la evidencia demuestra que el logro de los objetivos recomendados sigue siendo subóptimo para estos pacientes 2 . Las complicaciones relacionadas con la DM, macroangiopáticas y microangiopáticas incluidas la nefropatía, la retinopatía, la neuropatía, los accidentes cerebrovasculares y las enfermedades cardiovasculares, están aumentando en paralelo con las altas tasas de DM no controlada o produciéndose en corto tiempo 3 . La hemoglobina glicosilada (HbA1c) refleja los niveles de glucosa en sangre durante los últimos 120 días y es el biomarcador de referencia para la evaluación del control de la DM y la predicción de complicaciones graves 4 .…”
Section: Introductionunclassified
“…El manejo de la DM no solo se limita a los medicamentos, sino que requiere un enfoque multidimensional, que incluye aspectos relacionados con el estilo de vida (dieta, ejercicio físico, autocontrol) y seguimiento continuo 3 , así como, educación diabetológica para aprender a conocer la enfermedad y a vivir con ella. De acuerdo con la Asociación Americana de Diabetes, el óptimo manejo de la DM requiere un enfoque organizado, sistemático y la participación de un equipo coordinado de profesionales dedicados a la atención sanitaria que trabajen en un entorno donde la atención de alta calidad centrada en el paciente sea una prioridad y a la vez recomienda la incorporación del farmacéutico al equipo de atención 5 .…”
Section: Introductionunclassified